The Effects of the Growth of Peer-to-Peer (P2P) Lending Financial Technology Companies on the Performance of Conventional Liability Company Banks in Indonesia - Ariyanti, Bertha Zalfitri; Munawar (Contemporary Studies in Economic, Finance and Banking, 2025)
Previous research tends to show different results regarding the impact of fintech on banking performance. Therefore, the aim of this research is to examine the impact of fintech peer to peer (P2P) landing as a competitor on banking performance in Indonesia within the scope of conventional Persero banking. This research uses the ECM (Error Correction Model) regression test method where the research object used is conventional state-owned banks in Indonesia for the 2018-2022 period. The dependent variable is banking performance using ROA, LDR and BOPO, while the independent variable is peer to peer lending which uses the number of borrower accounts and loan amount, and there are control variables namely bank size (size) and CAP. The research results show that P2P Lending is not yet disruptive and cannot become competition that threatens the performance of state-owned banks in Indonesia.